Communications Trend Radar 2021. Denialism, Virtual Corporate Communications, Sustainable Communications, Digital Nudging & Voice Interaction - Ansgar Zerfaß; Stefan Stieglitz; Sünje Clausen; Daniel Ziegele; Karen Berger (Akademische Gesellschaft für Unternehmensführung & Kommunikation, 2021)
In recent months, the world has changed faster than ever. It's not easy for communications managers to keep track of all these changes, not to mention advise their top management and adjust corporate communications accordingly. Therefore, a research team from Leipzig University and University of Duisburg-Essen has conducted the first comprehensive trend study and identified the most relevant trends in management, society and technology. For 2021 the following trends will be relevant: Denialism, Virtual corporate communications, Sustainble corporate communications, Digital Nudging, Voice Interaction. – – Die Welt hat sich in den vergangenen Monaten noch einmal schneller verändert als zuvor. Für Kommunikationsverantwortliche ist es nicht einfach, all diese Veränderungen im Blick zu behalten. Und darüber hinaus auch die Geschäftsführung zu beraten und die eigene Abteilung darauf einzustellen. Deshalb hat ein Forscherteam der Universität Leipzig und Unviersität Duisburg-Essen erstmals eine umfangreiche Trend-Studie durchgeführt und die wichtigsten Trends in den Bereichen Management, Gesellschaft und Technologie identfiziert. Für 2021 sind das die folgenden Trends: Denialismus, Virtuelle Unternehmenskommunikation, Nachhaltigkeit in der Kommunikation, Digital Nudging, Voice Interaction.
Keywords: 650